KNOWLEDGE SHARING, INNOVATION CAPABILITY AND PUBLIC SECTOR PERFOMANCE IN INDONESIA - Dwi Irawan; Mudrifah Mudrifah (UNUSA Press, 2022)
This study aims to investigate the impact of knowledge sharing, innovation capability on the public sector performance in Indonesia. This study's data consisted of all Regional Work Units from various provinces in Indonesia. The data is analyzed using Structural Equation Modeling (SEM) with PLS 3.0 tools. The result shows that tacit knowledge sharing does not affect on innovation capability, but explicit knowledge sharing positively affects on innovation capability of public sector organizations. Furthermore, the innovation capability affects the organizational performance, which means that new ideas, new services, and improving the quality of services carried out by public sector organizations can improve organizational performance.